Vibratory Power Flow Analysis of a Gear-Housing-Foundation Coupled System - Yafeng Ren; Shan Chang; Geng Liu; Liyan Wu; Haiwei Wang (Shock and Vibration)
The marine gearbox is usually installed on a vibration isolation system in order to reduce oscillation transmitted to the ship foundation. However, researches on vibration transmission in the gear-housing system and isolation system are currently independent. With the increasing requirement of lower vibration, a coupled model needs to be built to control the vibration propagation from a view of the whole system. Considering the mesh transmission error excitation of a gear pair, a flexible gear-housing-foundation coupled impedance model is constructed in this paper, and the vibratory power flow of the whole system is calculated. Power transmissions between three different gearbox installation configurations, that is, rigid installation, single-stage isolation, and double-stage isolation, are compared. Taking the single-stage isolation configuration as an example, parameter influences on the vibration of the foundation are studied. Results show that double-stage isolation can achieve lower vibration than single-stage isolation; decrease in bearing stiffness or Young’s modulus of isolator will yield better vibration isolation performance; housing damping and isolator damping are beneficial to vibration reduction.